Microbiological analysis of water contamination in faucet piping and dental equipment in health units in Maceió, Alagoas (Research, Society and Development, 2023)
The objective of the research was to evaluate the level of contamination of water from dental equipment and taps by: heterotrophic bacteria, Coliforms and Pseudomonas spp. Sampling and microbiological parameters were defined according to Ordinance No. 2914/2011 of the Ministry of Health. For microorganism research, the filtering membrane method was used, according to APHA. Of the seven samples analyzed, he found the presence of heterotrophic bacteria in four, with countless heterotrophic bacteria in the triple syringe, pen and hose of the equipment. He observed that there was contamination by thermotolerant coliforms in the water of all evaluated objects: faucet, triple syringe, pen and equipment hose. In the triple syringe, in turn, it was seen that 71.4% of the samples were contaminated in the EC medium and 57.1% showed coliform growth in the EMB medium. Analyzing the bacteria of the coliform group, it is noticed that all the equipment evaluated, at some point, had contamination of fecal origin, in particular the triple syringe, which only the sample of a water sample did not prove to be contaminated. The research showed the need for greater rigor in the quality control of the water in the offices so that the population is not at the mercy of infections due to this lack of asepsis.